2021
DOI: 10.19206/ce-133872
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the technical condition of SO-3 engine turbine blades using an impulse test

Abstract: The paper presents the effects of the application of an experimental impulse test as a method of diagnosis of the technical condition of an SO-3 engine turbine blade fitted in a TS-11 Iskra aircraft. The aim of the test was to investigate the frequency characteristics of the blades and discuss differences between the frequency spectrum of the investigated component before and after its damage. The acoustic response measurements were performed to the signal generated by an impact hammer on the fully functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…This means that all violations, damages, or changes in the structure, even the minimal ones such as microcracking, change the vibration and acoustic signal parameters generated during standard operation or by deliberate excitation, e.g. during tests [15,18]. Therefore, it can be concluded that vibroacoustic diagnostics is a potentially effective method of determining the dynamic properties of elements made out of composite materials; especially in the aspect of assessing their technical condition and detecting structural damage.…”
Section: Wprowadzeniementioning
confidence: 99%
See 1 more Smart Citation
“…This means that all violations, damages, or changes in the structure, even the minimal ones such as microcracking, change the vibration and acoustic signal parameters generated during standard operation or by deliberate excitation, e.g. during tests [15,18]. Therefore, it can be concluded that vibroacoustic diagnostics is a potentially effective method of determining the dynamic properties of elements made out of composite materials; especially in the aspect of assessing their technical condition and detecting structural damage.…”
Section: Wprowadzeniementioning
confidence: 99%
“…Oznacza to, że wszelkie naruszenia, uszkodzenia, zmiany w strukturze, nawet te minimalne o charakterze mikropęknięć powodują zmianę parametrów odpowiednio sygnału drganiowego i akustycznego generowanych zarówno podczas standardowej eksploatacji jak i poprzez celowe wzbudzanie np. podczas badań [15,18]. Można więc wywnioskować, że diagnostyka wibroakustyczna jest potencjalnie skuteczną metodą wyznaczenia własności dynamicznych elementów kompozytowych -szczególnie w aspekcie oceny ich stanu technicznego i detekcji uszkodzeń w strukturze.…”
Section: Wprowadzenieunclassified
“…rotating machines (Bouaouiche et al, 2023; Chen et al, 2016; Jałowiecki et al, 2021; Shim et al, 2021), but also with the use of appropriate excitation also of elements which do not generate vibrations during normal operation, e.g. composite housing elements (Katunin et al, 2015;, beams or turbine blades (Milewicz et al, 2021). Most of the physical systems occurring in reality are characterized by non-linearity, which meet the assumptions of linearity only in the case of vibrations with low amplitudes.…”
Section: Introductionmentioning
confidence: 99%